Children of The Shapis and The Clash. Creative cultural proposal in Lima - Miramont, Lucie (2019)
The independent musical scene of Lima encompasses political issues or refers to the Peruvian identity. This article touches on particular aspects of this alternative scene. From my standpoint, the artistic and political dimensions being very much imbricated, the study naturally leads us to look at the social dynamics at play in Peru. It intends to start from an in-depth analysis of the different influences of the artists in order to understand what inspires them to create and how their inspiration is converted into original and hard-hitting creation songs.